The Penguin new writing in India - Behl, Aditya; Nicholls, David (Penguin Books, 1994)
Contributors to the Penguin New Writing in India include well-known names - Amrita Pritam, Satyajit Ray, Shashi Tharoor - alongside distinctive new voices, in a volume that combines the perspective of an anthology with the pioneering freshness of a literary magazine.